2005
DOI: 10.1021/la0505770
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Metal Ions on Monolayer Collapses

Abstract: A Langmuir monolayer of stearic acid on pure water and in the presence of certain divalent metal ions such as Cd and Pb at pH approximately 6.5 of the subphase water collapses at constant area, while for other divalent ions such as Mg, Co, Zn, and Mn at the same subphase pH the monolayer collapses nearly at constant pressure. Films of stearic acid with Cd, Pb, Mn, and Co in the subphase (at pH approximately 6.5) have been transferred onto hydrophilic Si(001) using a horizontal deposition technique, just after … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
55
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(55 citation statements)
references
References 28 publications
0
55
0
Order By: Relevance
“…. This 'spike' appears also for fatty acids and is interpreted as buckling and subsequent folding of the monolayer [29], or as the result of an effective mmA reduction caused by the nucleation and growth of 3D structures [27]. For liquid crystals the 'spike' is indicating crystallization [66].…”
Section: Langmuir Isothermsmentioning
confidence: 99%
See 1 more Smart Citation
“…. This 'spike' appears also for fatty acids and is interpreted as buckling and subsequent folding of the monolayer [29], or as the result of an effective mmA reduction caused by the nucleation and growth of 3D structures [27]. For liquid crystals the 'spike' is indicating crystallization [66].…”
Section: Langmuir Isothermsmentioning
confidence: 99%
“…Different mechanisms as, e.g. the 'constant pressure collapse' (without the occurrence of a 'spike' in the respective isotherm) and the 'constant area collapse' are discussed in connection with the presence of different divalent metal ions in the water subphase [27,28]. Furthermore, it is demonstrated that the film collapses after the sharp increase of the surface pressure up to a value of $60 mN m À1 with a clear 'spike' followed by a pseudo-plateau region of slightly increasing p. The 'spike' is interpreted to indicate the buckling and subsequent folding of the monolayer, and the pseudo-plateau is considered to be a region where a trilayer forms by a roll-over mechanism of the previously existent monolayer [29].…”
Section: Introductionmentioning
confidence: 99%
“…D uring the form a tion o f m onolayers the com petition betw een the first two forces plays the key role w hile the im portance o f the third grow s as the surface density is increased, as is expected. G row th o f L angm uir m onolayers o f fatty acids w ith the em ergence o f different structural phases at different surface concentrations or surface pressures has been thoroughly studied [21], as has been the dynam ics at very high n values, i.e., collapse [22][23][24][25][26][27]. However, even basic questions regarding the long-term dynam ics o f L angm uir m onolayers at low er "uttam.basak@saha.ac.in talokmay.datta@saha.ac.in surface pressure in the purported "stable" zones, such as the specific differences in dynam ics o f m onolayers that destabil ize through a desorption-dom inated (DD) m echanism from those undergoing a nucleation-dom inated (ND) destabilization have not been addressed, and the m ajor destabilizing force am ong the above three has not been identified.…”
Section: Introductionmentioning
confidence: 99%
“…For example, there are many factors which change the collapse of stearic acid from spikelike to plateaulike [38]. Usually in the literature only general changes caused by a specific experimental factor in the course of the π-A isotherms and in the collapse pressure are described.…”
Section: Discussionmentioning
confidence: 99%